Viabilidade do aproveitamento do lixo urbano da cidade de Maceió como alternativa energética. - Santos, Daniele Souza dos (2009)
Due to the consolidation of the capitalist model, technological progress and consequently the excessive consumption of disposable products, has become the great volume of solid waste generated by society, thus creating serious environmental and public health. Beside this problem, the sharp rise in the price of fossil fuels and the possibility of depletion makes it a great demand for alternative energy sources that are renewable, abundant and economically viable. In this context, the use of municipal solid waste as an alternative source of energy emerges as one of the options appropriate for the biogas generated by the decomposition of organic waste is mainly composed by methane (CH4), one of the main greenhouse effect gases trainers and has a high potential energy. This work will focus the exploitation of the urban solid residues as alternative source of energy, mainly in its use as electric energy, identifying your benefits. The main available in the market and used technologies in Brazil for the conversion of the garbage in electric energy will also be identified, characterizing its benefits and impacts that each one can bring to the environment. Moreover, the proposals will be seen that stimulate the use of biogas as renewable energy.